Reporter molecules for nanosized lyophilic dispersions. 2,6-Dychloro-4-(2,4,6-triphenylpyridinium-1-yl) phenolate in aqueous micellar solution of colloidal surfactants - Isaenko, Yu.V.; Vodolazkaya, N.A.; Mchedlov-Petrossyan, N.O. (Functional Materials, 2006)
The behavior of a reporter molecule, the solvatochromic dye 2,6-dichloro-4(2,4,6-triphenylpyridinium-1-yl)phenolate, was studied in aqueous micellar solutions of anionic, nonionic, and cationic surfactants. The possibility of utilization of this molecular probe as a combined indicator for monitoring of polarity and electrical potential of interfaces in lyophilic nanosized dispersions was demonstrated.